Investigasi Pengetahuan, Keterampilan Dan Implementasi Teknologi Informasi dan Komunikasi (TIK) Guru Matematika SMA/MA Di Kabupaten Tanjung Jabung Barat - Ana Rasyidah; Jefri Marzal; Damris M (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2015)
The development of science and information technology has changed paradigm of learning from conventional (teacher – centered) to a learning based on information and communication technology (ICT). This shift affects the teacher roles from information resources and expert in conventional teaching into facilitator, guidance an organizer in multimedia based teaching. Therefore, teachers should be able to utilize and integrate ICT. So, teachers have to have knowledge, skills and able to implement ICT in the teaching of their subjects. The purposes of this research are to measure ICT knowledge, skill and its implementation in mathematics teaching and to identify factors and obstacles affecting math teachers use ICT in the classroom of senior high school in Tanjung Jabung Barat. The method of this research is quantitative research by using descriptive analysis. Data were collected using questionnaire of teachers knowledge, skill and implementation ICT. The research populations are mathematics teachers of senior high school in Tanjung Jabung Barat and all are as the sample of this research. This is because the total populations are relatively small. The result of this research showed that the levels of teacher’s knowledge and implementation are both ‘low’, while teacher skill is at ‘medium’ level. From the background of respondents involving the status of civil servant, experience, gender, age and workshop or ICT course, it seems doesn’t effect the teachers competence. The obstacles that affect teacher in using ICT for teaching is lack of ICT facilities at school.